Mechanical ventilation and nursing management for a case of severe asthma complicated with intrinsic positive end-expiratory pressure (1例重症哮喘合并内源性呼气末正压的机械通气救治护理体会) - LIU Yan (刘雁); ZHOU Jie (周洁); HAN Jianping (韩建萍); ZHANG Ning (张宁); LIU Huan (刘欢); (冯亚静); (唐玲); (杜英华) (中西医结合护理)
This article summarized the mechanical ventilation and nursing management for a case of severe asthma complicated with intrinsic positive end-expiratory pressure. The mechanical ventilation was adopted to relieve the symptoms of dyspnea. Comprehensive interventions including vital signs monitoring, noninvasive ventilation nursing, basic nursing, nutrition support, psychological care were carried out to reduce the complication during treatment and improve the recovery of the patient. (本文总结1例重症哮喘合并内源性呼气末正压患者机械通气救治和护理经验。机械通气能有效改善患者呼吸困难的症状, 同时配合病情观察、无创通气护理、基础护理、营养支持以及心理干预等优质护理措施, 积极预防并发症, 促进患者早日康复。)